dS6K-regulated cell growth is dPKB/dPI(3)K-independent, but requires dPDK1. - Radimerski, T.; Montagne, J.; Rintelen, F.; Stocker, H.; van Der Kaay, J.; Downes, C.P.; Hafen, E.; Thomas, G. (Nature Cell Biology, 2002)
Genetic studies in Drosophila melanogaster underscore the importance of the insulin-signalling pathway in controlling cell, organ and animal size. Effectors of this pathway include Chico (the insulin receptor substrate homologue), dPI(3)K, dPKB, dPTEN, and dS6K. Mutations in any of these components have a striking effect on cell size and number, with the exception of dS6K. Mutants in dS6K affect cell size but not cell number, seemingly consistent with arguments that dS6K is a distal effector in the signalling pathway, directly controlled by dTOR, a downstream effector of dPI(3)K and dPKB. Unexpectedly, recent studies showed that dS6K activity is unimpaired in chico-deficient larvae, suggesting that dS6K activation may be mediated through the dPI(3)K docking sites of the Drosophila insulin receptor. Here, we show genetically, pharmacologically and biochemically that dS6K resides on an insulin signalling pathway distinct from that of dPKB, and surprisingly also from that of dPI(3)K. More striking, despite dPKB-dPI(3)K-independence, dS6K activity is dependent on the Drosophila homologue of the phosphoinositide-dependent protein kinase 1, dPDK1, demonstrating that both dPDK1, as well as dTOR, mediated dS6K activation is phosphatidylinositide-3,4,5-trisphosphate (PIP3)-independent.